Effect of substituting pork fat for sacha inchi oil (Plukenetia volubilis L.) and banana flour on cooking performance, fat content, peroxide value and general acceptability of hamburger (Agroindustrial Science, 2021)
The consumer trend is to return to the consumption of healthy and natural foods without affecting their daily diet, in current eating habits, meat products that are easy to prepare and consume such as hamburgers stand out. In the present investigation the effect of substituting pork fat for two concentrations of sacha inchi oil (Plukenetia volubilis L.) (5 and 10%) and three concentrations of banana flour (Musa paradisiaca L.) (2%, 4% and 6%) variety Inguiri on the cooking performance, the content fat, peroxide value and general acceptability of beef burger. The effect of substituting pork fat for sacha inchi oil and banana flour for cooking performance, fat content and peroxide index was significant (p < 0.05). Treatment with substitution of pork fat for 5% sacha inchi oil and 6% banana flour allowed to obtain the lowest value of the peroxide index (12.17 meq O2/kg), the best general acceptability (6.27 points), fat (17.23%) and cooking yield (90.56%) in beef burger (Bos taurus).
Keywords: sacha inchi; banana flour; fat content; peroxide index; cooking performance